THE EFFECT OF GRATITUDE ON THE SUBJECTIVE WELL-BEING OF EMPLOYEES AT THE CLASS IIB STATE DETENTION CENTER IN PACITAN - Aldyansyah, Titho; Wibowo, Padmono (Universitas Nusa Cendana, 2026)
This study aims to examine the effect of gratitude on the subjective well-being of employees at the Class IIB State Detention Center in Pacitan. Using a quantitative survey approach, data were collected from all employees through validated and reliable measurement scales, and analyzed using simple regression techniques. The findings indicate that gratitude has a positive influence on employees’ subjective well-being. Employees who demonstrate higher levels of gratitude tend to experience greater happiness, life satisfaction, and overall psychological well-being. This suggests that positive emotional attitudes play an important role in supporting mental health within the correctional work environment. In conclusion, fostering gratitude among employees can contribute to improved well-being and a more positive organizational climate. Therefore, it is recommended that detention centers implement mental development programs that encourage the practice of gratitude as part of efforts to enhance employee welfare and performance. Keywords: Gratitude; Subjective Well-Being; Employee; State Detention Center